Functional characterization and regulation of abiotic stress-responsive genes (GmNAC081 and SbMATE) in plants - Pimenta, Maiana Reis (2015)
The onset of leaf senescence is a highly regulated developmental change that is controlled by both genetics and the environment. Senescence is triggered by massive transcriptional reprogramming, but functional information about its underlying regulatory mechanisms is limited. In the current investigation, we performed a functional analysis of the soybean (Glycine max) osmotic stress- and endoplasmic reticulum (ER) stress-induced NAC transcription factor GmNAC081 during natural leaf senescence using overexpression studies and reverse genetics. GmNAC081- overexpressing lines displayed accelerated flowering and leaf senescence but otherwise developed normally. The precocious leaf senescence of GmNAC081-overexpressing lines was associated with greater chlorophyll loss, faster photosynthetic decay and higher expression of hydrolytic enzyme- encoding GmNAC081 target genes, including the vacuolar processing enzyme (VPE), an executioner of vacuole-triggered programmed cell death (PCD). Conversely, VIGS-mediated silencing of GmNAC081 delayed leaf senescence and was associated with reductions in chlorophyll loss, lipid peroxidation and the expression of GmNAC081 direct targets. Promoter–reporter studies revealed that the expression pattern of GmNAC081 was associated with senescence in soybean leaves. Our data indicate that GmNAC081 is a positive regulator of age-dependent senescence and may integrate osmotic stress- and ER stress-induced PCD responses with natural leaf senescence thorough the GmNAC081/VPE regulatory circuit. In addition to environmental stressors, many plant species are sensitive to micromolar concentrations of Al. In sorghum, aluminum resistance SbMATE gene is highly expressed at the apex of the radicle and encodes a membrane transporter belonging to MATE family (multidrug and toxic Compound Extrusion family), which is responsible for the efflux activated aluminum citrate. In this species the coding region of the aluminum tolerance gene is identical between tolerant and sensitive cultivars. In a polymorphism is found in the second intron, the MITE type transposable elements were detected in the promoter region, the number of repetitions MITE positively related tolerance. In this work, the analysis in silico showed typical SbMATE promoter sequences of eukaryotic promoters, as well as the presence of cis regulatory elements that confer tolerance in Arabidopsis. The absence of whole promoter activity in transformed Arabidopsis suggesting the presence of negative regulatory cis- elements repressing the activity in Arabidopsis or the presence of transcriptional silencing by RNA interference in Arabidopsis does not occur in sorghum. Deletions promoter showed that the repressors are located in sequence as the transposable element in the absence of this element, the promoter becomes active in every part regardless of the age of plant form. Prospecting for transcription factors that control the responsiveness of SbMATE Sorghum gene and analysis of the interaction between likely transfatores with SbMATE promoter, were performed using mono-hybrid system in yeast and demonstrated the need for obtaining a new cDNA library made for a more appropriate for this plant kit, besides the use of different cloning vectors for analysis of iterations.